Cooperação e atividade: a construção das regras de trabalho na produção de feijão agroecológico de um assentamento de reforma agrária - Camila Rolim Laricchia (2022)
Cooperative organization is an alternative of struggle and resistance of workers to capitalist competition, which conforms selfish and isolated. To overcome this condition, organized peasant movements encourage agricultural cooperation in rural settlements. However, these experiences face difficulties in reconciling individual and collective interests. In order to reflect on a development strategy for cooperation in agroecological production that is capable of overcoming current limits, this thesis analyzes collective production practices in the PDS Osvaldo de Oliveira, a rural settlement that resulted from the Landless Rural Workers Movement's (MST) struggle for land, located in Córrego do Ouro, Macaé district, in Rio de Janeiro. We aim to contribute analytically to studies on agricultural cooperation, theorizing about the ontological dynamics of cooperation and understanding details of subjective relationships in the production and use of work rules. Based on these theoretical analyses, a practical contribution that we intend is to support the formulation of development strategies for cooperation in rural settlements. For this, we analyzed the conception and use of work rules in agroecological bean production collectives composed of PDS Osvaldo de Oliveira settlers, we carried out a brief historical analysis of strategic decisions on agricultural cooperation by the MST and retrieved studies on cooperation and collective work, such as Chayanovian theory and Work Clinics (ergology, psychodynamics of work, activity clinic). We conclude that: collectives are composed of persons with particular interests that must be recognized; the formulation and transformation of work rules by the group, as well as the creation of trust devices, can mediate conflicts arising from inter-individual differences; as people are different and the rules always have a risk of not being followed, conflicts are part of the collective work; cooperation will be facilitated if people have dialogic and conflict mediation skills; and the development of cooperation in agricultural production collectives can take longer than in other types of collectives, such as commercialization and machine sharing, since the formulation of work rules regarding participation and distribution of results is more complex. The results of the fieldwork showed that cooperation is a collective learning process about working together, that begins in the work experience itself and not through the indoctrination of the virtues of cooperation, and which can be maintained, expanded or even reversed depending on the subjective evaluations of the its results.